Me, My Prey and I: Embodiment and Empathy in the Dialogical Self of a Siberian Hunter - Giesser, Thorsten (Studia Psychologica: Theoria et praxis, 2008)
In this article I examine the non-verbal dialogues between Siberian hunters and their prey in order to explore how empathetic relationships affect the integrity of the dialogical self. Based on the ethnographic accounts of the anthropologist Rane Willerslev (2002, 2004a, 2004b, 2007) I show how the hunter maintains his human identity while he imitates the movements of his prey and thereby 'feels-into' the animal. Challenging the common idea that inner consistency and synthesis of voices holds the dialogical self together (e.g. Hermans and Kempen 1993), I argue that this case demonstrates how integrity can be maintained through inconsistent and discordant voices. In this discussion I emphasise the role of the body within the dialogical self and show how positions can be embodied in different parts and movements of the body. In order to clarify the significance of this case study for psychology, I then compare aspects of empathy and embodied positions in hunting with similar phenomena in Fogel et al.'s (2002) study of non-verbal dialogues in early infancy. Finally, this comparison invites us to re-consider the role of experienced-based, qualitative methods, such as participant observation, in studying the dialogical self.